2015
DOI: 10.1016/j.gde.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cell fate commitment during mammalian sex determination

Abstract: The gonads form bilaterally as bipotential organs that can develop as testes or ovaries. All secondary sex characteristics that we associate with ‘maleness’ or ‘femaleness’ depend on whether testes or ovaries form. The fate of the gonads depends on a cell fate decision that occurs in a somatic cell referred to as the ‘supporting cell lineage’. Once supporting cell progenitors commit to Sertoli (male) or granulosa (female) fate, they propagate this decision to the other cells within the organ. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 105 publications
1
85
0
2
Order By: Relevance
“…Combined, these data indicate that FGF9, activin and TGFβ act together to promote Sox9 transcription and some testicular characteristics in intact cultured XX gonads and limited expression of SOX9 and AMH protein. This conclusion is consistent with previous observations that activin/ TGFβ signalling is required for testis cord formation and Sertoli cell proliferation in E11.5-E12.5 XY gonads ) and the established role for FGF9 in testis development (Lin & Capel 2015). Although we observed increased Sox9, Cyp26b1 and Inhba transcription and some SOX9+ and AMH+ cells in FAT-treated XX gonads, Dhh was not upregulated, indicating that Sertoli cell development was restricted in this system.…”
Section: Growth Factors Fgf9 Activin and Tgfβ Promote Testicular Chasupporting
confidence: 93%
See 1 more Smart Citation
“…Combined, these data indicate that FGF9, activin and TGFβ act together to promote Sox9 transcription and some testicular characteristics in intact cultured XX gonads and limited expression of SOX9 and AMH protein. This conclusion is consistent with previous observations that activin/ TGFβ signalling is required for testis cord formation and Sertoli cell proliferation in E11.5-E12.5 XY gonads ) and the established role for FGF9 in testis development (Lin & Capel 2015). Although we observed increased Sox9, Cyp26b1 and Inhba transcription and some SOX9+ and AMH+ cells in FAT-treated XX gonads, Dhh was not upregulated, indicating that Sertoli cell development was restricted in this system.…”
Section: Growth Factors Fgf9 Activin and Tgfβ Promote Testicular Chasupporting
confidence: 93%
“…In mice, testis development is initiated by expression of the Y-chromosome-linked testis-determining gene Sry (sex-determining region of chromosome Y). SRY promotes pre-Sertoli cell proliferation and expression of the dominant male sex-determining transcription factor Sox9 (Sry-box containing gene 9), leading to commitment of bipotential pre-supporting cells to Sertoli cell development and testis differentiation (Lin & Capel 2015). As Sertoli cells proliferate, they organise into laminin-delineated testis cords that surround germ cells, thereby defining the interstitial space where steroidogenic Leydig cells differentiate (Lin & Capel 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sox9 is a direct effector of the mammalian somatic sex determination gene, Sry . Sry is a mammalian‐specific gene, while Sox9 is conserved among vertebrates 50. However, our recent analysis indicated that sox9b − an orthologue of the mammalian Sox9 expressed in the supporting cells − is not directly involved in testicular differentiation.…”
Section: Neofunctionalization Of Other Genes With Loss Of Germline Stmentioning
confidence: 96%
“…Gonadal differentiation into a testis or an ovary requires a delicate dosage balance in the timing and levels of expression of several genes [Lin and Capel, 2015]. In most mammalian embryos, the transient expression of SRY , which maps to the Y chromosome, triggers a cascade of gene interactions ultimately leading to the formation of a testis from the indifferent gonadal ridge [Larney et al, 2014].…”
Section: Introductionmentioning
confidence: 99%